SIZE DISTRIBUTION OF Cerithium rostratum SHELL USED BY CRUSTACEA BIRGUS IN COASTAL WATERS OF SUNGAI NIPAH IN PESISIR SELATAN PROVINCE WEST SUMATRA - Sri Wira Rahayu Ningsih; Afrizal Tanjung; Syafruddin Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study aims to determine the abundance, size distribution of Cerithium rostractum shells used Birgus in coastal waters of the Sungai Nipah in West Sumatra. This study was conducted in June 2015. Birgus was obtained from three different stations. The results showed that at the first station had the highest average of abundance is 13333.33 ind / Ha and the lowest average of abudance at station III that was 2266,667 ind/ Ha. There were 5 Birgus species namely B. rugosus, B. perlatus, B. perlatus, and species B. brevimanus with pereent abudance of 4.32% -61.11%. Shell size used by Birgus were grouped info 4 groups, namely the size of group 1 (<50mm), group 2 (50-80mm), group 3 (81-100mm), and group 4 (>10mm). Birgus shell size that is used most dominant came from size of 51-80mm and 81-100mm, in all station. The overall distribution pattern in the study site was 1.02 -1.71, meaning the tipe of distribution was spread clustered. Result of the F test on abudance showed a significant difference. The value of environmental parameters measured were in the range of : temperatures 29-30.5 0C, pH 7, salinity 30-32 ‰, and transparency of 100%. The parameter values is still were all still supporting to Birgus life.keyword: Birgus, abundance, shell size, Cerithium rostractum, distribution pattern, and Sungai Nipah